Spatial analysis of hypertension’s awareness, treatment and control in India: evidence from national family health survey 2019-21 - Priti; Rahul Kumar; Kunal Keshri; Ankit Gupta (BMC Public Health)
Abstract Background Being a primary contributor to cardiovascular diseases (CVDs), Hypertension is the leading cause of morbidity and mortality worldwide. Globally, around 4 billion people were estimated to have hypertension in 2019, resulting in 10 million deaths. However, the present study has been designed to explore hypertension awareness, control, and treatment dimensions in India. Data & methods Data were drawn from 1,551,191 respondents from the fifth round of India’s National Family Health Survey. Hypertension, by the World Health Organization, is defined as systolic blood pressure (SBP) ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg. The binary Logistic regression statistical method is employed to analyze the data, and the geospatial method—spatial autocorrelation has been used to explore the spatial relationship between variables of hypertension and spatial units. Results The results show a positive correlation between higher wealth position, urban residency, male gender, older age, and higher education levels with better knowledge and treatment of hypertension. On the other hand, people from worse socioeconomic origins, those living in rural areas, and members of particular social and religious groups have lower awareness and treatment levels. The findings also show that urban males are more likely to have managed hypertension, indicating that socioeconomic and geographic factors play a major role in the management of hypertension. Conclusion The study’s results highlight the urgent need for focused public health initiatives to address hypertension knowledge, management, and treatment differences. Better access to healthcare is necessary for the efficient management of hypertension, especially in underserved areas and among lower socioeconomic groups. Furthermore, public health initiatives should emphasize raising awareness and improving treatment compliance, drawing on information from socioeconomic and spatial assessments to guide the creation of policies and programs.